Large tumor suppressor 2 is a prognostic biomarker and correlated with immune infiltrates in colorectal cancer - Chengwen Zhao (Taylor & Francis Group, 2021)
Colorectal cancer (CRC) is a common malignancy that has both low 5-year survival and high prevalence. Immunotherapy has achieved impressive progress for treatment of CRC, but still faces huge challenges. Although large tumor suppressor 2 (LATS2) is well accepted to be related to cancer progression, the prognostic potential and immune response role of LATS2 expression in CRC remain unclear. To investigate the value of LATS2 for prognosis and immune infiltration, a retrospective study of 213 CRC patients was carried out. We determined the expression of LATS2 in tumor tissues by immunohistochemistry. The results indicated that LATS2 expression was down-regulated in CRC tissues and clearly related to tumor differentiation (P =0.002) and TNM stage (P =0.002). Low LATS2 expression and TNM stage were subsequently identified as significant independent predictors of prognosis in CRC by univariate and multivariate analyses. In Kaplan–Meier survival analyses, CRC patients with elevated LATS2 expression and early TNM stage had better overall survival. We further found that LATS2 was involved in the regulation of immune-related pathways and that its expression was positively related to tumor-infiltrating immune cells by GSEA, TIMER, and ssGSEA analyses. In summary, our data imply that LATS2 may act as a cancer suppressor gene and be correlated with clinical prognosis and immune infiltration in CRC. Thus, LATS2 may be applied as a novel biomarker for predicting clinical outcomes and immune infiltration levels in CRC.